Enabling Mobile Devices for Home Automation Using ZigBee - Olteanu, Alexandru-Corneliu; Oprina, George-Daniel; Tapus, Nicolae; Zeisberg, Sven (2013 19th International Conference on Control Systems and Computer Science, 2013)
Home automation systems are collections of interconnected devices for controlling various functions within a house, such as light control, heating, air conditioning, etc. Mobile devices are ideal in providing a user interface in a home automation system, due to their portability and their wide range of capabilities. They can communicate with a home automation network through an Internet gateway, but cannot directly communicate with devices in the network, as these devices usually implement low power communication protocols, such as ZigBee. We investigate several methods to equip an Android device with a dongle capable of ZigBee communication. We propose a scalable architecture, with three abstraction layers, that scales over multiple communication channels, such as the TCP channel, for communication with the gateway, and the USB channel, for direct communication with devices through the dongle. We test the application with two client devices running Android 4.0 and a mock home automation network consisting of a couple of ZigBee devices and a PC as gateway. We estimate the energy consumption of WiFi transfers over several typical use cases and we conclude that using ZigBee can prove beneficial in some cases, both in terms of functionality and performance.